Angular analysis of the decay B$^+$$→$ K$^+μ^+μ^-$ in proton-proton collisions at $\sqrt{s} =$ 8 TeV - CMS collaboration (2300 authors) (2018)
The angular distribution of the flavor-changing neutral current decay B$^+$$→$ K$^+μ^+μ^-$ is studied in proton-proton collisions at a center-of-mass energy of 8 TeV. The analysis is based on data collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5 fb$^{-1}$. The forward-backward asymmetry $A_{FB}$ of the dimuon system and the contribution $F_{H}$ from the pseudoscalar, scalar, and tensor amplitudes to the decay width are measured as a function of the dimuon mass squared. The measurements are consistent with the standard model expectations.